A Feasibility Study on Electric Taxis - Aquino, Diana Sylvia Z.; Batungbakal, Pia Marie S.; Cruz, Jennifer D. (Diliman, Quezon City College of Engineering, 2004)
With the worsening condition of air in the Philippines especially in urban areas, health problems due to air pollution have become a big issue in the country. Even the smallest effort to alleviate this problem is needed to continue to make the country inhabitable in the next decades. One alternative solution to improve the air sheds particularly in Metro Manila is to operate a taxi service using electric vehicles. Compared to gas-powered vehicles, electric vehicles are environment friendly as these do not emit gases that harm the atmosphere. The feasibility study of Clean Air Benefits (CAB) Company, a company with a vision of being the country;s number one provider of environment-friendly transportation solutions, was done to minimize the risk of project failure if implemented, to come up with accurate estimation of resources to be consumed,, to justify the investment, and to formulate a working plan for the project implementation. The feasibility study was comprised of four phases: market, technical, financial and socio-profitability analysis. The market study was done to determine the present and projected potential market of electric cars that will be used as taxis. The marketing expense was also identified in this phase. In the technical analysis, the different aspects of establishing a taxi company, including the associated costs, were determined. The financial study was done to present an overall financial background of establishing an electric taxi company, including the associated costs, were determined. The financial stud was done to present an overall financial background of establishing an electric taxi company in terms of cash requirements, profitability and cash flow. Lastly, the socio-economic effects of the taxi operation industry in relation to the individual, community and society were presented. Clean Air Benefits Company will only be deemed feasible if each of the four phases is feasible. The potential market area, the appropriate market segmentation, the total market share and the marketing plans were the main concerns of the market feasibility analysis. Since EVs are widely used in other countries, the internet was the main channel used for data gathering. Different government agencies were also consulted for other information essential to the project. To obtain first hand information about the company's market surveys were designed for passengers and taxi drivers. Finally, a marketing plan for the company was created and evaluated. F Actors sensitive to the service's inherent characteristics were deliberated on and after in-depth market analysis, it was concluded that the CAB company is feasible for the market analysis phase of the study. The technical analysis of this feasibility study included decisions between different alternatives for the source or supplier of the electric cars, the logistics on how these cars are to be transported to the Philippines, the procedure and cost of shipping, the spare parts requirement for the cars' maintenance, its inventory system and suppliers, the cars' operating and charging schedules, the space requirements for the company's charging sites, and the manpower requirement, including their wages and benefits. All associated costs were determined to estimate the company's start-up cost. Using value engineering, Feel Good Cars from Canada was chosen to be the supplier of electric vehicles and other car parts that are specific to electric vehicles. A single supplier was also chosen to be the company's tooling and local spare parts supplier. Also, the optimal schedule determined through dynamic programming was for the cars to be operational from 6:30 - 9:00 AM, 11:30 - 2:00 PM, 4:30 - 7:00 PM. The cars will be charged from 9-11:30 AM, 2:4:30 PM, and from 7-12 midnight in order to achieve full charge for the next day. Two charging sites will be used by the company, one each in Manadaluyong and in Makati. The space requirements for the faculties were determined and layouts for the charging sites were established. The total cost of fixed assets for the company amounted to Php 129,292,474.26 while the total operating expenses for the fifteen year study period was Php 239,789,520.36. The financial feasibility analysis of the project required the determination the total project cost and the form and sources of financing to be used by the company. Financial projections, pro-forma income statements, statements of cash flows, and balance sheets were created for the 15 year study period. Tax considerations were identified, after which financial analysis was performed through tests of liquidity, debt service, operational efficiency, total debt coverage, financial leverage, and capital investment. Lastly, sensitivity analysis was performed using break-even analysis and the discounted cash flow model. All financial tests posted positive results and it was concluded that CAB Company is financially feasible. In determining the company's impact on the socio-economic community, cost-benefit analysis was performed given the various benefits and costs the company would provide to society. Three socio-economic criteria were used: net present value method (NPV); internal rate of return (IRR); and benefit-cost ratio (B/C Ratio). The analysis includes identifying and analyzing the constraints to the project's success, the benefits to society, and to other externalities. At a social discount rate of 15%, all three criteria showed the project as socially acceptable. This indicates that CAB Company is socially profitable. All phases of the study had positive results and were proven to be feasible. Thus, it can be concluded that Clean Air Benefits Company is feasible.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Clean Air Benefits (CAB) Company; Electric automobiles; Taxicabs; Participatory monitoring and evaluation (Project management)